(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Corporate Governance has fast emerged as a benchmark forjudging corporate excellence in the context of national and internationalbusiness practices. From guidelines and desirable code of conduct some decadeago, corporate governance is now recognized as a paradigm for improvingcompetitiveness and enhancing efficiency and thus improving investors‘confidence and accessing capital, both domestic as well as foreign. What isimportant is that corporate governance has become a dynamic concept and notstatic one. Sound CorporateGovernance Policies are important to the creation of shareholders value andmaintaining the confidence of customers and investors alike. The Bank’sCorporate Governance Policies are designed to ensure the independence of theBoard of Directors (BoDs) and its ability to effectively supervise management’soperation of the Bank. This paper examines the Corporate Governance Policies ofCommercial banks in India which are classified into Public Sector Banks andPrivate Sector Banks. Private Sector banks are further classified into Old PrivateSector Banks and New Private Sector Banks in the study. The Governance Policieshave been assessed with the help of five parameters namely, Reasons for thewritten code of Corporate Governance, Availability of Corporate GovernancePolicies, Distribution of Related Material to concerned parties, Issues in Codeof conduct and Other components of Corporate Governance. Moreover, the studyempirically tests the difference in the Corporate Governance Policies betweenthe Public Sector banks and Private Sectors banks; and, also between the OldPrivate Sector Banks and New Private Sector Banks in India.